2009
DOI: 10.1063/1.3095505
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of amorphous InGaZnO4 films doped with Mn

Abstract: Amorphous InGaZnO4 (a-IGZO) films doped with various concentrations of Mn have been fabricated by using pulsed-laser deposition technique. Optical, electrical, and magnetic properties of the prepared Mn-doped a-IGZO films were investigated. The resistivity, carrier concentration, and carrier mobility of the a-IGZO films were found to be, respectively, increased, decreased, and enhanced by Mn doping. Moreover, the optical transmission is slightly increased in the visible range and the optical band gaps are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…In the present case, all of the a-IGZO thin films were found to be of the n-type. It is noteworthy that the ranges of the electrical property values were similar to those reported by Liu et al 9 The data showed that resistivity (ρ) decreased (from 7.0 × 10 −3 to 4.7 × 10 −3 −cm) but the carrier concentration (n) increased (from 2.6 × 10 19 to 5.0 × 10 19 /cm 3 ) with the increase of the substrate temperature (T s ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In the present case, all of the a-IGZO thin films were found to be of the n-type. It is noteworthy that the ranges of the electrical property values were similar to those reported by Liu et al 9 The data showed that resistivity (ρ) decreased (from 7.0 × 10 −3 to 4.7 × 10 −3 −cm) but the carrier concentration (n) increased (from 2.6 × 10 19 to 5.0 × 10 19 /cm 3 ) with the increase of the substrate temperature (T s ).…”
Section: Resultssupporting
confidence: 83%
“…a-IGZO films are known to be advantageous over other polycrystalline oxide semiconductors in uniformity. 9 I. From the AFM images and RMS roughness values (0.23 ∼ 0.27 nm), we could conclude that the morphology of the thin films was not much affected within the RT ∼ 300 • C substrate temperature range.…”
Section: Resultsmentioning
confidence: 74%
“…In the present case, all of the a-IGZO thin films were found to be of the n-type. It is noteworthy that the range of electrical values is similar to that reported by Liu et al [21]. The data show that the Hall mobility decreased and the carrier concentration increased as the working pressure increased.…”
Section: Resultssupporting
confidence: 80%
“…Very recently, the experimental results for Mn doped InGaZnO 4 were reported [72]. It was found that the conductivity decreases while the carrier mobility increases with Mn content (up to 2.5 at.% of Mn).…”
Section: V3 Role Of the Dopant's Electronic Configurationmentioning
confidence: 99%